Aku dalam Tuhan: Implikasi Teologi Proses pada Era Kontemporer - Suhermanto Ja’far (Universitas Islam Negeri Mataram, 2012)
Theological implications in social lives are still worth analyzed. This paper discusses the authentic image of man as I in the relationship with God and the world. These relationships affect the nature of the world and the world to change the nature of God. The implications of the inclusion of God in the world is God’s presence to the world and the world is affected God. Immanent God is the God who is present in every human being, every living being, and the universe. Every human being is unique and as I am in the uniqueness of God is present. In the directionality that God wanted man and the world become “like Him”, they are united with him; He is involved in the principles and ways of working people and the world. Even though God is in everything and everything is in God, it does not mean that everything is identical, or equal with God. God that is “above” and present “in” the world to make people as I was in the Lord.